Surfing with sound: an ethnography of the art of no-input mixing - Chamberlain, Alan (2018)
The idea of No-Input Mixing may appear at first difficult to understand, after all there is no input, yet artists, performers and sound designers have used a variety of approaches using such feedback systems to create music. This paper uses ethnographic approaches to start to understand the methods that people employ when using no-input systems, and in so doing tries to make the invisible, visible. In unpacking some of these techniques we are able to render understandings, of what at first appears to be a random and autonomous set of sounds, as a set of audio features that are controlled, created and are able to be manipulated by a given performer. This is particularly interesting for researchers that involved in the design of new feedback-based instruments, Human Computer Interaction and aleatoric-compositional software.